The pore domain of the nicotinic acetylcholine receptor: molecular modeling, pore dimensions, and electrostatics - Sankararamakrishnan, R; Adcock, C; Sansom, M (Elsevier, 1996)
The pore domain of the nicotinic acetylcholine receptor has been modeled as a bundle of five kinked M2 helices. Models were generated via molecular dynamics simulations incorporating restraints derived from 9-Å resolution cryoelectron microscopy data (Unwin, 1993; 1995), and from mutagenesis data that identify channel-lining side chains. Thus, these models conform to current experimental data but will require revision as higher resolution data become available. Models of the open and closed states of a homopentameric α7 pore are compared. The minimum radius of the closed-state model is less than 2 Å; the minimum radius of the open-state models is ∼6 Å. It is suggested that the presence of "bound" water molecules within the pore may reduce the effective minimum radii below these values by up to ∼3 Å. Poisson-Boltzmann calculations are used to obtain a first approximation to the potential energy of a monovalent cation as it moves along the pore axis. The differences in electrostatic potential energy profiles between the open-state models of α7 and of a mutant of α7 are consistent with the experimentally observed change in ion selectivity from cationic to anionic. Models of the open state of the heteropentameric Torpedo nicotinic acetylcholine receptor pore domain are also described. Relatively small differences in pore radius and electrostatic potential energy profiles are seen when the Torpedo and α7 models are compared.